ISOTOPIC COMPOSITION OF CARBON IN DIAMONDS OF DIAMONDITES: RECORD OF MASS FRACTIONATION IN THE UPPER MANTLE - Maruoka T.; Koeberl C.; Kurat G.; Dobosi G. (My University, 2004)
Carbon isotope data have been obtained for diamonds in diamondites (framesites, polycrystalline diamond) of unknown origin (presumably from southern Africa), which contain minor amounts of garnet (plus rare clinopyroxene). The carbon isotope abundance ratios show wide inter- and intra-sample ranges. The δ13C variations of diamonds from diamondites with “peridotitic” or “eclogitic” garnets are indistinguishable from each other, with a range from −3.2 to −27.9‰, and a peak around −18‰, indicating a depletion in 13C relative to most silicate-bearing single crystal diamonds. This 13C depletion could have been produced by mass fractionation of C from an isotopically homogeneous mantle source in a C-O-H fluid system. Fluids traveling between regions of varying redox conditions in the mantle could have provided the necessary vehicle. The variations of δ13C can be explained by different degrees of oxidation during the fluid/melt ascent.